DETERMINANTS OF ISLAMIC BANKING FINANCIAL PERFORMANCE: ANALYZING THE ROLE OF CSR, ZAKAT, AND GCG IN INDONESIA AND MALAYSIA - Syiami, Suci Siti; Muflih, Muhammad (Universitas Airlangga, 2024)
Although the Islamic banking sector is expanding rapidly, it still needs to improve its financial performance in order to compete with conventional banking. This study attempts to investigate how corporate social responsibility (CSR), zakat, and good corporate governance (GCG) affect the financial performance of Islamic banking in Indonesia and Malaysia from 2015 to 2021. Using the quantitative method of panel data regression, the study discovered that, simultaneously, CSR, zakat, and GCG have a significant impact on the financial performance of Islamic banking in both countries. Partially, only GCG has a noticeable influence while the other two do not. The results of this study encourage Islamic banks to consistently develop CSR, zakat, and GCG in every aspect of their operations and lead the industry.